The relevance of communal altruism for sexual minority men in contemporary contexts. Issue 4 (6th August 2022) - Skakoon‐Sparling, Shayna; Card, Kiffer G.; Novick, Jake R.; Berlin, Graham, W.; Lachowsky, Nathan J.; Adam, Barry; Brennan, David J.; Sang, Jordan M.; Noor, Syed W.; Cox, Joseph; Moore, David M.; Grace, Daniel; et al.
Abstract: There are many reasons why individuals engage in prosocial behavior; communal sexual altruism is based on the notion that some practice safer sex in the interest of promoting the well‐being of their community/in‐group. Given that definitions of what constitutes "safer sex" have changed with advances in human immunodeficiency virus (HIV) prevention, we investigated the importance of communal sexual altruism (herein "altruism") among urban gay, bisexual, and other sexual minority men (GBM) in the contemporary context. Using a sample of 2449 GBM we examined the association of both safer‐sex‐related attitudes (e.g., HIV treatment optimism–skepticism) and behaviors (e.g., condomless anal sex [CAS]) with altruism scores. Higher altruism scores were associated with a lower likelihood of CAS and a greater frequency of discussing HIV status with new partners. These findings demonstrate that many GBM are motivated to engage in several kinds of behaviors that improve the well‐being of their in‐group (i.e., the GBM community).